Testing, numerical analysis and design of stainless steel equal-leg angle section beams. (March 2022) - Behzadi-Sofiani, Behnam; Gardner, Leroy; Wadee, M. Ahmer
Abstract: The stability and design of stainless steel equal-leg angle section members subjected to uniaxial bending are studied herein. An experimental investigation, comprising material testing, initial geometric imperfection measurements and physical tests on hot-rolled austenitic stainless steel equal-leg angle section beams is first presented. The test results are then used to validate shell finite element models developed within ABAQUS, which are in turn used to undertake numerical parametric studies that consider both hot-rolled and cold-formed equal-leg angle section beams in austenitic, duplex and ferritic stainless steel with a wide range of slenderness values. Recent studies have shown that for angles under major-axis bending, both lateral-torsional and local buckling can arise, while under minor-axis bending, lateral-torsional buckling and Brazier-type flattening can occur. When designing for major-axis bending according to Eurocode 3, both local and lateral-torsional buckling are considered; it is shown herein that equal-leg angle sections under major-axis bending can be designed using a normalised slenderness based on the minimum of the local and lateral-torsional elastic buckling moments, while also considering their ratio. Under minor-axis bending, however, in comparison with the current provisions in Eurocode 3 that only require cross-section checks, it is shown that both safer and more accurate resistance predictions can be achieved when account is taken for lateral-torsional buckling and Brazier-type flattening. New design proposals for stainless steel equal-leg angle section beams, covering both major- and minor-axis bending, are therefore developed. The proposed design rules offer substantially more accurate and consistent resistance predictions compared to existing codified design rules. The reliability of the new design provisions, with a recommended partial safety factor γ M 1 = 1.1, is verified following the procedure provided in EN 1990.